Sexual Humor in Dickens' Works - Inda Nur Abida, Fithriyah; Mustofa, Ali (KnE Social Sciences, 2022)
This paper attempts to investigate a sexual selection-based argument about the significance of humor in courtship. The huge range of Dickensian sexual humor suggests that the extroversion of female characters is associated with their inferior position. Females were formerly under-represented in producing humor. Jokes and humorous acts were primarily associated with males, particularly in the domain of sexual humor. Dickens’ use of sexual humor is evidence for the critic and becomes a valuable tool for revealing gender stereotypes in the 19